1998
DOI: 10.1002/(sici)1097-4547(19981201)54:5<691::aid-jnr14>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine, in the presence of tyrosinase, covalently modifies and inactivates tyrosine hydroxylase

Abstract: Dopamine has been implicated as a potential mediating factor in a variety of neurodegenerative disorders. Dopamine can be oxidized to form a reactive dopamine quinone that can covalently modify cellular macromolecules including protein and DNA. This oxidation can be enhanced through various enzymes including tyrosinase and/or prostaglandin H synthase. One of the potential targets in brain for dopamine quinone damage is tyrosine hydroxylase, the rate-limiting enzyme in catecholamine biosynthesis. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(82 citation statements)
references
References 32 publications
3
76
0
3
Order By: Relevance
“…The absence of substrate nitration in tyrosinase/O 2 /NO-mediated reactions with either L-dopa or dopamine may document a significantly different method of converting o-diphenols to o-quinones than that employed by peroxidase/H 2 O 2 . This possibility highlights the importance of several recent studies documenting the presence of tyrosinase in the brain (47)(48)(49)(50)(51) and reports that enzyme activity (11,19,52) and melanogenesis are enhanced by NO modulating tyrosinase gene expression via the cGMP pathway (19,52). In our investigations we found that the amount of substrate oxidized in reactions containing both tyrosinase and NO was less than additive, suggesting enzyme inhibition.…”
Section: Figsupporting
confidence: 76%
“…The absence of substrate nitration in tyrosinase/O 2 /NO-mediated reactions with either L-dopa or dopamine may document a significantly different method of converting o-diphenols to o-quinones than that employed by peroxidase/H 2 O 2 . This possibility highlights the importance of several recent studies documenting the presence of tyrosinase in the brain (47)(48)(49)(50)(51) and reports that enzyme activity (11,19,52) and melanogenesis are enhanced by NO modulating tyrosinase gene expression via the cGMP pathway (19,52). In our investigations we found that the amount of substrate oxidized in reactions containing both tyrosinase and NO was less than additive, suggesting enzyme inhibition.…”
Section: Figsupporting
confidence: 76%
“…DA can auto-oxidize to the ortho-quinone that can readily react with cysteine residues in proteins such as DA transporters [38]. In synaptosomal preparations the, auto-oxidation of DA leads to the inhibition of DA uptake by the DAT [3] and inhibition of glutamate uptake by the glutamate transporter [2], and in the presence of tyrosinase, DA induces the covalent modification and inactivation of TH [41]. These harmful effects of DA auto-oxidation may result from the covalent modification of cysteinyl residues of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It must be realized that metabolic deamination of dopamine and its O-methyl metabolite by MAO results in H 2 O 2 as a byproduct. Also, dopamine oxidation to dopamine quinone, stimulated by tyrosinase, is accompanied by the inactivation of tyrosine hydroxylase (226). Dopamine (aut)oxidation also probably explains the observed inactivation of parkin by dopamine (227), and dopamine quinone has been found to covalently modify Cys residues of the dopamine transporter (228).…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%